2022
DOI: 10.1002/vjch.202200001
|View full text |Cite
|
Sign up to set email alerts
|

A review on application of marine algae as green corrosion inhibitors in acid medium

Nabilah Ismail,
Siti Mariana Mujad,
Mohammad Fakhratul Ridwan Zulkifli
et al.

Abstract: Corrosion is significant and continuous issue that causes serious problem on environment, properties, our lives and leads to economic losses. So, prevention of corrosion requires more attention. Metal corrosion inhibitors, both inorganic and synthetic, are used to prevent and slow down corrosion, although these inhibitors are hazardous. Thus, green corrosion inhibitors which both environmentally and economically are likely the solution to this problem. A lot of research has been done to discover good corrosion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 29 publications
0
0
0
Order By: Relevance
“…Many plant extracts have been shown to inhibit corrosion. Previous extracts experimentally investigated include Marine algae [190,191], baicalin derivatives [192], Angelica sinensis [193], vernonia amygdalina [194], citrus aurantium [195], nicotiana tabacum [196], African breadfruit [197], combretum bracteosum [198], and buddleia perfoliate [199]. Some researchers concluded that since most plant chemical synthesis occurs in leaves, the main sources of corrosion inhibitors also converge in leaves.…”
Section: Green Inhibitorsmentioning
confidence: 99%
“…Many plant extracts have been shown to inhibit corrosion. Previous extracts experimentally investigated include Marine algae [190,191], baicalin derivatives [192], Angelica sinensis [193], vernonia amygdalina [194], citrus aurantium [195], nicotiana tabacum [196], African breadfruit [197], combretum bracteosum [198], and buddleia perfoliate [199]. Some researchers concluded that since most plant chemical synthesis occurs in leaves, the main sources of corrosion inhibitors also converge in leaves.…”
Section: Green Inhibitorsmentioning
confidence: 99%